Towards inclusionary and diversity-sensitive public health: the consequences of exclusionary othering in public health using the example of COVID-19 management in German reception centres and asylum camps - Kayvan Bozorgmehr; Jacob Spallek; Marie Tallarek (BMJ Global Health)
The German government’s response to the COVID-19 pandemic has been predominantly considered wellfounded. Still, the practice of mass quarantine in reception centres and asylum camps has been criticised for its discrimination of refugees and asylum seekers. Building on the concept of othering, this article argues that processes of othering are structurally anchored in German asylum regulations and they have further pervaded public health measures against COVID-19. The practice of mass quarantine made the negative consequences of exclusionary othering for public health particularly noticeable. In the light of recent data indicating this measure to be epidemiologically, legally and ethically insufficient, we apply the concept of othering to public health and discuss (1) exclusionary, (2) inclusionary and (3) diversity-sensitive approaches to public health. We finally conclude that a shift of perspective from exclusion to inclusion, from subordination to empowerment and from silencing to participation is urgently required.